A phase I/II trial of intraoperative breast radiotherapy in an Asian population: 10-year results with critical evaluation. (4th June 2020) - Kawamura, Mariko; Itoh, Yoshiyuki; Kamomae, Takeshi; Sawaki, Masataka; Kikumori, Toyone; Tsunoda, Nobuyuki; Ito, Junji; Shimoyama, Yoshie; Satake, Hiroko; Naganawa, Shinji
Abstract: Although phase III trials have been published comparing whole breast irradiation (WBI) with accelerated partial breast irradiation (APBI) using intraoperative radiotherapy (IORT), long-term follow-up results are lacking. We report the 10-year follow-up results of a prospective phase I/II clinical trial of IORT. The inclusion criteria were as follows: (i) tumor size <2.5 cm, (ii) desire for breast-conserving surgery, (iii) age >50 years, (iv) negative margins after resection and (v) sentinel lymph node-negative disease. A single dose of IORT (19–21 Gy) was delivered to the tumor bed in the operation room just after wide local excision of the primary breast cancer using a 6–12 MeV electron beam. Local recurrence was defined as recurrence or new disease within the treated breast and was evaluated annually using mammography and ultrasonography. A total of 32 patients were eligible for evaluation. The median patient age was 65 years and the median follow-up time was 10 years. Two patients experienced local recurrence just under the nipple, out of the irradiated field, after 8 years of follow-up. Three patients had contralateral breast cancer and one patient experienced bone metastasis after 10 years of follow-up. No patient experienced in-field recurrence nor breast cancer death. Eight patients had hypertrophic scarring at the last follow-up. There were no lung or heart adverse effects. This is the first report of 10-year follow-up results of IORT as APBI. The findings suggest that breast cancer with extended intraductal components should be treated with great caution.